Trabalhos restantes ineditos da Comissão Geologica do Brazil (1875-1878) - (:unkn) unknown (Museu Paraense Emilio Goeldi, 1898)
Works comprising the results of two expeditions by Ch. Fred. Hartt in the Lower Amazon region in 1870 and 1871.
Keywords: Geologia e Geografia; Baixo Amazonas; CNPQ::CIENCIAS BIOLOGICAS